Numerical simulation study on the influence of artificial reefs on the instantaneous collision with seabed based on the explicit finite element method. (1st October 2022) - Wang, Jiahao; Nie, Zhaoyi; Zhang, Jiating; Zhu, Lixin; Xie, Wude; Liang, Zhenlin; Jiang, Zhaoyang
Abstract: The deposition of artificial reef (AR) is a complicated systematic project. The instantaneous impact and subsidence between ARs and seabed will reduce the effective volume of AR. This study presents the effects of ARs on seabed subsidence based on explicit finite element method. The cut-opening ratio on reef bottom, weights and incident angles of ARs were used as the influencing factors, and the respective terminal velocities were used as the initial conditions to simulate the instantaneous collision process. The research results showed that the subsidence effect of ARs with a larger volume ratio (0.50) and material density (7896 kg/m 3 ) in the seabed will be more obvious, and the rate of effective facility volume can be reduced to 79.1%. The change of incident angle affected the deformation region after AR subsidence. The indexes of the subsidence ratio and the rate of effective facility volume should be used simultaneously to measure the extent of subsidence. In addition, the maximum stress monitoring results of AR in subsidence process verified that the current strength standard of 25 MPa can meet the safety needs of AR deposition. This study aims to provide a scientific reference for the structural design and release scheme of AR. Highlights: The ANSYS-AUTODYN was used to study the effects of artificial reefs on the seabed subsidence. The subsidence of artificial reef was affected by the volume, material and incident angle, and the cut-opening ratio on the reef bottom had little effect on it. The maximum settlement and the rate of effective facility volume were used to evaluate the subsidence degree of AR.